Avaliação de uma intervenção de hábitos de vida para trabalhadores da Atenção Básica: um estudo qualitativo - Coelho, Marilia (Universidade Federal de São Carlos, 2020)
INTRODUCTION: Primary care workers assume an important role in terms of the multiplication of health information, however the overload in their work environment makes disease prevention and health promotion programs that include them indispensable. OBJECTIVE: To evaluate the perception of effectiveness and feasibility of a program to support lifestyle changes for health professionals in Primary Care. METHODS: This is a qualitative study carried out in the city of São Carlos, SP, part of a randomized clinical study carried out in the Basic Health Units (UBS) and Family Health Units (USF) in the municipality. The program consists of an intervention with six meetings of approximately 40 minutes, the first being a pre-assessment, the four consecutive meetings addressing themes that pertain to behavior change, such as: Tips and Benefits; Barriers; Relapses and Saboteurs' Thoughts, using different strategies in order to support the change in behavior of the workers involved, and the sixth meeting consisted of a post evaluation and qualitative interview. Twenty health professionals were interviewed, aged over 18 years, who reached 85% of frequency in the program offered. A semi-structured interview was conducted at the end of the program's participation, by trained interviewers, in which the individuals answered, according to their opinion, what their level of satisfaction with the program was, how effective it was, what their suggestions for improvement about it and about the knowledge acquired with the program. The interviews took place at his workplace and were recorded using the interviewer's smartphone recorder, with the interviewee's consent. The data were analyzed through content analysis by Bardin and Minayo, with categorization of the main domains identified in the participants' statements. RESULTS: From the workers 'reports, it was identified that the program is perceived as viable, of quality, effective and that it contributes to the improvement of the participants' lifestyle. CONCLUSION: The behavior change program was effective and feasible in the perception of primary care health professionals.
Evaluation of a lifestyle intervention for primary healthcare workers: a qualitative study
Keywords: Saúde do trabalhador; Atenção primária à saúde; Exercício; Dieta saudável; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA